2009
DOI: 10.1007/s12550-009-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone, deoxynivalenol and aflatoxin B1 and their metabolites in pig urine as biomarkers for mycotoxin exposure

Abstract: Methods to determine zearalenone (ZEA), deoxynivalenol (DON), aflatoxins (AF) and their metabolites in pig urine were developed as biomarkers for pig exposure to the mycotoxins in feed. Urine samples were incubated with β-glucuronidase to cleave conjugates, extracted and cleaned-up with solid phase and immunoaffinity columns, followed by HPLC with UV and fluorescence detection. Good recoveries (83-130%), low variation (2-10%), and low detection limits (0.3-9.9 ng/ml) were obtained. The results of controlled AF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…The metabolism and tissue distribution of AFB 1 in pigs were studied by Lüthy et al (1980), and the major excretory route was found to be the feces (51-65% of the dose administered) but also urine was also an important excretory route. Actually, both AFM 1 and AFB 1 were detected in pig urine samples and AFM 1 was always found at higher concentrations in all studies (Thieu and Pettersson, 2009). In fact, urinary AFB 1 and AFM 1 are often used as biomarkers for aflatoxin exposure in pigs.…”
Section: Pigsmentioning
confidence: 88%
“…The metabolism and tissue distribution of AFB 1 in pigs were studied by Lüthy et al (1980), and the major excretory route was found to be the feces (51-65% of the dose administered) but also urine was also an important excretory route. Actually, both AFM 1 and AFB 1 were detected in pig urine samples and AFM 1 was always found at higher concentrations in all studies (Thieu and Pettersson, 2009). In fact, urinary AFB 1 and AFM 1 are often used as biomarkers for aflatoxin exposure in pigs.…”
Section: Pigsmentioning
confidence: 88%
“…Moreover, it is the main source feed for livestock (such as pigs and cattle) in Vietnam. In humans and animals, aflatoxins in urine have been used as a marker of exposure, and it has been shown that there is a correlation between aflatoxin intake and serum concentrations, as well as serum concentrations and urine AFM 1 concentrations [ 32 , 38 ]. Therefore, a rigorous investigation is necessary to assess the full impact of AFB 1 and AFM 1 on plant, animal and human health in Son La province.…”
Section: Discussionmentioning
confidence: 99%
“…One study in two pigs found only up to 16% of a dose of AFB 1 fed to the animals could be detected in the urine [ 31 ]. In another pig trial in Vietnam, approximately 23% of ingested AFB 1 was converted to AFM 1 and excreted in the urine [ 32 ]. Another older study found that the average AFM 1 concentration in pig urine was 2.29 ng/ml after feeding 12.7 μg/kg AFB 1 over 12 weeks [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Urine. Aflatoxin M 1 has been identified as the main metabolite of AFB 1 in urine for humans and laboratory animals, indicating that urine is one of the most important pathways to excrete AFB 1 from the body (Hsieh et al, 1994;Thieu and Pettersson, 2009). Last, we evaluated AFB 1 and AFM 1 excretion in the urine (Figure 2G and H).…”
Section: Aflatoxin Solubilization Absorption and Excretion In The Gmentioning
confidence: 99%